Using Dysphonic Voice to Characterize Speaker’s Biometry - Gómez, Pedro; San Segundo, Eugenia; Mazaira, Luis M.; Álvarez, Augustin; Rodellar, Victoria (Language and Law / Linguagem e Direito, 2017)
Phonation distortion leaves relevant marks in a speaker’s biometric profile. Dysphonic voice production may be used for biometrical speaker characterization. In the present paper phonation features derived from the glottal source (GS) parameterization, after vocal tract inversion, is proposed for dysphonic voice characterization in Speaker Verification tasks. The glottal source derived parameters are matched in a forensic evaluation framework defining a distance-based metric specification. The phonation segments used in the study are derived from fillers, long vowels, and other phonation segments produced in spontaneous telephone conversations. Phonated segments from a telephonic database of 100 male Spanish native speakers are combined in a 10-fold cross-validation task to produce the set of quality measuremen ts outlined in the paper. Shimmer, mucosal wave correlate, vocal fold cover biomechanical parameter unbalance and a subset of the GS cepstral profile produce accuracy rates as high as 99.57 for a wide threshold interval (62.08-75.04%). An Equal Error Rate of 0.64 % can be granted. The proposed metric framework is shown to behave more fairly than classical likelihood ratios in supporting the hypothesis of the defense vs that of the prosecution, thus offering a more reliable evaluation scoring. Possible applications are Speaker Verification and Dysphonic Voice Grading.